Lipid-based nutrient supplementation in the first 1000 d improves child growth in Bangladesh: a cluster-randomized effectiveness trial - Dewey, Kathryn G; Mridha, Malay K; Matias, Susana L; Arnold, Charles D; Cummins, Joseph R; Khan, Md Showkat Ali; Maalouf-Manasseh, Zeina; Siddiqui, Zakia; Ullah, Md Barkat; Vosti, Stephen A (© 2017 American Journal of Clinical Nutrition, 2018)
This article was published in the American Journal of Clinical Nutrition [© 2017 American Journal of Clinical Nutrition ] and the definite version is available at : https://doi.org/10.3945/ajcn.116.147942. The Journal's website is at: http://ajcn.nutrition.org/content/early/2017/03/08/ajcn.116.147942.full.pdf